Precision Oncology and Cancer Biomarkers (Human Perspectives in Health Sciences and Technology, 2022)
This open access book reflects on matters of social and ethical concern raised in the daily practices of those working in and around precision oncology. Each chapter addresses the experiences, concerns and issues at stake for people who work in settings where precision oncology is practiced, enacted, imagined or discussed. It subsequently discusses and analyses bioethical dilemmas, scientific challenges and economic trade-offs, the need for new policies, further technological innovation, social work, as well as phenomenological research. This volume takes a broad actor-centred perspective as, whenever cancer is present, the range of actors with issues at stake appears almost unlimited. This perspective and approach opens up the possibility for further in-depth and diverse questions, posed by the actors themselves, such as: How are cancer researchers navigating biological uncertainties? How do clinicians and policy-makers address ethical dilemmas around prioritisation of care? What are the patients’ experiences with, and hopes for, precision oncology? How do policy-makers and entrepreneurs envisage precision oncology? These questions are of great interest to a broad audience, including cancer researchers, oncologists, policy-makers, medical ethicists and philosophers, social scientists, patients and health economists.